Zur Grammatik von Referenz und Episodizitaet - Hansen, Björn (Specimina philologiae Slavicae, 1996)
The work provides significant real and current insights into the functions of Russian verbal and nominal groups. At the same time, it brings perspectives-rich methodological impulses through the psychologically oriented empirical investigation methods of the individual-language, especially of Slavic linguistics.